2007
DOI: 10.1038/sj.onc.1210848
|View full text |Cite
|
Sign up to set email alerts
|

1p36 is a preferential target of chromosome 1 deletions in astrocytic tumours and homozygously deleted in a subset of glioblastomas

Abstract: Astrocytic, oligodendroglial and mixed gliomas are the commonest gliomas in adults. They have distinct phenotypes and clinical courses, but as they exist as a continuous histological spectrum, differentiating them can be difficult. Co-deletions of total 1p and 19q are found in the majority of oligodendrogliomas and considered as a diagnostic marker and a prognostic indicator. The 1p status of astrocytomas has not yet been thoroughly examined. Using a chromosome 1 tile path array, we investigated 108 adult astr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
1
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 42 publications
1
74
1
7
Order By: Relevance
“…In this study, oligodendrogliomas presented only two haplotypes, mainly whole loss and, in a minority of cases, arm retention, whereas the other patterns were found in glioblastoma multiforme. Other studies have reported that whole 1p loss is rare in astrocytomas and, conversely, that partial loss restricted to the 1p36 region is more frequent in anaplastic astrocytomas (22%), glioblastomas (34%) 8 and oligoastrocytomas (60%). 12 We found 1p telomeric loss limited to the 1p36 region in 25% of the astrocytomas and 35% of the oligoastrocytomas.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In this study, oligodendrogliomas presented only two haplotypes, mainly whole loss and, in a minority of cases, arm retention, whereas the other patterns were found in glioblastoma multiforme. Other studies have reported that whole 1p loss is rare in astrocytomas and, conversely, that partial loss restricted to the 1p36 region is more frequent in anaplastic astrocytomas (22%), glioblastomas (34%) 8 and oligoastrocytomas (60%). 12 We found 1p telomeric loss limited to the 1p36 region in 25% of the astrocytomas and 35% of the oligoastrocytomas.…”
Section: Discussionmentioning
confidence: 97%
“…Complete 1p19q loss is associated with the classical oligodendroglial phenotype and has been shown to be correlated with significantly longer overall and progression-free survival, whereas partial 1p telomeric loss is mostly found in astrocytic tumors and is associated with a poor prognosis. 8,20 Thus, in practice, analyses of 1p and 19q loss analyses should distinguish between cases of whole loss and telomeric loss, based on the use of appropriate FISH probes, comparative genomic hybridization or microsatellite marker amplification by PCR, exploring the entire chromosomal arms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RTK-independent activation of this pathway in glioblastoma can occur via mutation or amplification of PIK3CA (p110a) [46,47], and PIK3CD (p110d) is also overexpressed in some gliomas [48]. Other amplified regions containing oncogenes, for example AKT3 [22,49] and CCND2 [22,27].…”
Section: Amplificationmentioning
confidence: 99%